Orthopädische Schuhtechnik - Greitemann, Bernhard; Schievink, Frank (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Orthopedic footwear care is a means that orthopedists and traumatologists in the German-speaking regions have at their disposal due to the long-standing tradition in the crafts sector. The prescription for orthopedic care is based on the patient’s functional deficit: e. g. foot deformities, degenerative joint diseases of the foot, knee and hip, trauma, metabolic, neurological and rheumatic diseases, tumors, inflammatory transformation, skin and nail diseases, pressure calluses, static alteration and leg length differences. Orthopedic footwear supplies are an essential component of conservative and postoperative orthopedic and traumatic therapy. Orthopedic shoe modifications include orthopedic insoles, alterations on ready-to-wear shoes, foot orthoses or prosthetic foot orthoses, custom orthopedic footwear, standard orthopedic footwear (training shoes, semi-orthopedic shoes, protective footwear) and orthopedic specialty footwear.
Keywords: konservative Orthopädie; Orthopädietechnik; Einlagenversorgung; orthopädische Schuhversorgung